Trabalhadores galegos no Douro vinhateiro - Pereira, Gaspar Martins (2016)
Due to the shortage of local workers, the intensivework in the Douro vineyards has depended for centuriesin the attraction of the people from the poor neighbouringregions. With the development of the tradeof the fortified wines of the Douro, from the late seventeenthcentury on, when the preferences of the Britishmarket stood out, the planting of new vineyards spreadand the need for workers to their granjeio increased.At that time, the Douro attracted many galegos (Galicians),especially for big chores of surribas, plantations,construction of terraces, cavas and the grapeharvest, which in the larger estates, came to concentratehundreds of workers. For nearly two centuries, untilthe beginning of the twentieth century, every yearthousands of galegos workers reached the Douro indroves, accompanied by contractors who traded a fewmonths working on a farm. After the destruction causedby phylloxera, when it was necessary to rebuild theentire regional vineyard, many surribas and new vinesplantations were carried out by galegos. After thefirst decades of the twentieth century, the galegosstopped to looking for work in the Douro. Disappearedand forgotten, the galegos left, however, an indeliblemark not only on the monumental vineyard landscapeof the Alto Douro but also in its people, habits that aregrafted on local traditions in ways of saying and doing,gastronomy, religiosity, music or popular imagination.In this brief communication, a synthetic historicalperspective of the long term, we intend to place thework of the galegos in the construction and reconstructionof the Douro wine region.